2017
DOI: 10.3390/met7100388
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assisted Casting of an AM60 Based Metal Matrix Nanocomposite, Its Properties, and Recyclability

Abstract: An AM60 magnesium alloy nanocomposite reinforced with 1 wt % of AlN nanoparticles was prepared using an ultrasound (US) assisted permanent-mould indirect-chill casting process. Ultrasonically generated cavitation and acoustic streaming promoted de-agglomeration of particle clusters and distributed the particles throughout the melt. Significant grain refinement due to nucleation on the AlN nanoparticles was accompanied by an exceptional improvement in properties: yield strength increased by 103%, ultimate tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 45 publications
(55 reference statements)
2
53
0
Order By: Relevance
“…As a result, mechanical properties of the metal matrix nanocomposite are enhanced [8,21]. In the nanocomposites processed by ultrasonic melt treatment, metal matrices are largely focused on aluminum [116,117,[123][124][125][126][127][128], magnesium alloys [6,[129][130][131], and transition metal alloys [8]. Typical nanoparticle reinforcers [8,[132][133][134] include SiC, Al 2 O 3 , and various carbon polymorphs (e.g., graphene, carbon nanotubes, and diamond nanoparticles).…”
Section: Cavitation In Molten Metal-nanoparticle Composite Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, mechanical properties of the metal matrix nanocomposite are enhanced [8,21]. In the nanocomposites processed by ultrasonic melt treatment, metal matrices are largely focused on aluminum [116,117,[123][124][125][126][127][128], magnesium alloys [6,[129][130][131], and transition metal alloys [8]. Typical nanoparticle reinforcers [8,[132][133][134] include SiC, Al 2 O 3 , and various carbon polymorphs (e.g., graphene, carbon nanotubes, and diamond nanoparticles).…”
Section: Cavitation In Molten Metal-nanoparticle Composite Systemsmentioning
confidence: 99%
“…The grain refining effect of the introduced nanoparticles is very clearly illustrated when, as a part of the EU project EXOMET, a die-casting alloy AM60 was reinforced with 1 wt% AlN nanoparticles [127]. The AM60 is a commercial alloy used in the automotive industry from which, for example, steering wheels, seat frames, or housings are die-cast.…”
Section: Hall-petchmentioning
confidence: 99%
“…In a broader study of the AM60-AlN system, a Hall-Petch relationship with grain size was found despite the very large number density of nanoparticles [12].…”
Section: Ust Assisted Grain Refinement Of An Am60 Alloy Containing Almentioning
confidence: 99%
“…(a) (b) Figure 11. Microstructure and grain size of (a) AM60, 1277 ± 300 m and b) AM60+AlN, 85 ± 6.2 m [12].…”
Section: Ust Assisted Grain Refinement Of An Am60 Alloy Containing Almentioning
confidence: 99%
See 1 more Smart Citation